Impact of diabetes mellitus on tuberculosis treatment outcomes: a cohort study in Bengaluru, India - Gudegowda, Kishore Shettihalli; Jagadish, Deepak Murthy H.; Sobagaiah, Ranganath T. (International Journal Of Community Medicine And Public Health, 2024)
Background: Tuberculosis (TB) remains a significant global health challenge, particularly in regions with a high prevalence of diabetes mellitus (DM). This study aims to evaluate the impact of DM on the treatment outcomes of TB patients in Bengaluru, India. Methods: In this cohort study, we examined 592 patients with smear-positive pulmonary TB, half of whom had a comorbid diagnosis of DM. Conducted in the Bruhat Bengaluru Mahanagara Palike area, the study included patients registered under the national TB elimination programme (NTEP). Data were collected on demographic characteristics, treatment adherence, sputum positivity, and treatment outcomes over six months. Results: The study revealed a high prevalence of DM among TB patients. Significant associations were observed between DM and various challenges, including higher rates of sputum positivity, poor adherence to anti-TB and anti-diabetic medications, increased adverse drug reactions (ADRs), and a higher default rate. TB patients with DM had a 1.5 times higher risk of unsuccessful treatment outcomes compared to non-diabetics. Furthermore, the risk of poor outcomes, particularly relapse, increased substantially in the TB-DM group during the six-month follow-up. Conclusions: Our findings highlight the crucial need for integrated TB and DM management strategies. This includes routine DM screening for TB patients, personalized treatment regimens, and enhanced patient education and support. These measures are essential for improving treatment outcomes in TB patients with comorbid DM.